A Study on Different Applications of M-governance and its Security - Banerjee, D; Karforma, SK (International Journal of Computer Sciences and Engineering, 2025)
Mobile governance (m-governance) provides all the government services in a convenient manner. The proper establishment of e-governance has a great impact on the initiatives taken for m-governance. M-governance can be presumed as an extension of e-governance. Mobile computing and different communication technology are used for delivering different government services and for accessing information from both the central and state governments. M-governance provides greater flexibility to all the users of different domains. Security is the most important issue in today’s world. This paper gives an overview of the architecture and framework of m-governance as well as various applications of government initiatives on a mobile platform with different aspects of providing security to all these projects. These mobile applications can be successfully instigated and sustained only if the m-governance framework can implement the optimum security structure. It can convince all the participants about its authenticity, integrity, acceptability, as it is solely responsible for securing all the public information from unauthorized access, by using different security techniques like encryption, digital signature, digital certificates, watermarking etc.